Experimental therapies in Alzheimer's disease: the development and use of mouse models - Westaway, David (Henry Stewart Talks, 2007)
Animal models and AD research, Role in identifying pathological pathways, biomarkers and candidate therapies, Design of models and associated technical parameters, Process of transgenesis, Developing mouse models for beta-amyloid precursor protein mutations, TgCRND8 mice, Transgenic approaches for investigating Tau mutations, Exploring environmental modifiers of beta-amyloid pathobiology, Candidate chemical risk-factor for sporadic AD, Potential of ''smart'' beta-amyloid-directed interventions
Archived at 2021/02/25